Dicrostonyx hudsonius - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Dicrostonyx hudsonius (Pallas, 1778). Nova Spec. Quad. Glir. Ord., p. 208. TYPE LOCALITY: Canada, Labrador. DISTRIBUTION: Labrador and N. Quebec (Canada). COMMENT: A distinctive species placed in its own monotypic subgenus, Misothermus; see Guilday, 1968, Univ. Colo. Stud. Ser. Earth Sci., No. 6, and Rausch, 1977, in Sokolov, ed., [Adv. Mod. Theriot], Acad. Sci. U.S. S.R., Nauka, Moscow, pp. 162- 177. ISIS NUMBER: 5301410008073001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 483, DOI: 10.5281/zenodo.7353034